Sol-Gel Synthesis and Characterization of Mesoporous TiO2 Modified with Transition Metal Ions (Co, Ni, Mn, Cu) - O. O. Kelyp; I. S. Petrik; V. S. Vorobets; N. P. Smirnova; G. Ya. Kolbasov (Хімія, фізика та технологія поверхні)
Mesoporous nanosized titania films and powders modified with Co2+, Ni2+, Mn3+ and Cu2+ ions have been produced by templated sol-gel method and characterized by optical spectroscopy, XRD, and BET surface area measurment. After calcinations at 400°C, XRD patterns showed the anatase nanocrystalline phase formation (8–20 nm). The characteristic bands of Co2+ and Co3+ in octahedral and tetrahedral oxygen environment registered in diffusion reflectance spectra indicated the formation of Co3O4 spinel phase; crystallization of M/TiO2 powders after heat treatment at 650°C led to an appearance of absorption bands belonging to Ni2+ or Mn3+ ions in an octahedral environment. Band gap energy and the position of flat band potentials were estimated by photoelectrochemical measurements. The films doped with transition metals possessed higher photocurrent quantum yield than that for undoped samples.